Emerging giants China and India in the world economy - Eichengreen, Barry J.; Gupta, Poonam; Kumar, Rajiv, 1951- (Oxford : Oxford University Press, 2010)
This work explores the rapid growth and development of China and India and looks at some of the issues this raises for the countries concerned, and their impact on the world economy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: China -- Economic conditions -- 2000-; India -- Economic conditions -- 1991-; Economic development -- China; Economic development -- India; China -- Foreign economic relations; India -- Foreign economic relations